Beekeeping – A sweet reward to farmers under Farmer FIRST Programme in Punjab - Kaur, Prabhjot; Kumar, Pankaj (Indian Farming, 2021)
The Farmer FIRST Programme as a concept of ICAR is developed as farmers in a centric role for research problem identification, prioritization and conduct of experiments and its management in farmers’ conditions. The focus is on farmer’s Farm, Innovations, Resources, Science and Technology (FIRST). Farmers tend to face problems related to production and natural resource management but they might not have found the solutions to overcome them. In such situations, Farmer FIRST Programme is an opportunity for the researchers, extension professionals and farmers to work together and find appropriate ways through assessing different solutions.